ANTI-B-CELL THERAPY AT IMMUNE INFLAMMATORY RHEUMATIC DISEASES: EFFICACY AND TOLERABILITY IN 229 PATIENTS - L. P. Ananieva; S. K. Soloviyov; T. V. Beketova; V. I. Vasiliev; O. A. Antelava; E. N. Aleksandrova; O. A. Koneva; M. E. Tsanyan; O. V. Desinova; O. A. Logvinenko; A. V. Volkov; A. N. Helkovskaya-Sergeeva; et al. (Научно-практическая ревматология, 2014)
Objective: to assess the efficacy and tolerability of Rituximab treatment in patients with serious immune inflammatory rheumatic diseases (IRD) like systemic lupus erythematosus (SLE), systemic sclerosis (SS), systemic vasculitis (SV), Sjogren syndrome (SjS), dermatomyositis/polymyositis (DM/PM).Subjects and methods. The clinical efficacy has been analyzed in 229 patients with IRD: SLE (n=97), SV (n=50), SS (n=40), SjS (n=23) and DM/PM (n=19). Rituximab treatment was accompanied by administration of glucocorticoids and/or immunosuppressive drugs. Most patients demonstrated resistance to or low tolerability of standard therapy. Efficacy of treatment was analyzed in each group with the criteria relevant for each disease. To compare clinical response to the treatment between the groups we used gradations accepted by international registries: complete (good) response, partial response, no response. Average duration of monitoring comprised 72 (1–288) weeks after the first introduction of Rituximab. Average Rituximab dose administered to patients over the period of monitoring was low and varied from 1.6±0.84 in DM/PM to 3.1±1.75 in SV. About 80% of patients received one or two courses of Rituximab except for patients with SS (half of them received three and more courses).Results. «Complete response» was observed in 50.6%, «partial response» – in 35% of patients. Rituximab courses provided positive dynamics in clinical scores and allowed to reduce supportive dose of glucocorticoids and to lower the dose or withdraw of immune-stimulating drugs. Multiple Rituximab courses provided stable and longlasting effect. Recurrences were observed less frequently, whereas efficacy of the therapy increased during a year and longer. Occurrence of adverse events and mortality rate were comparable to data of other national Rituximab registries.Conclusion. The results of the study may prove administration of Rituximab in patients with resistance to standard therapy